Group Counseling Using The Dispute Cognitive Technique To Reduce People Pleaser Behavior Among Students At Mtsn Tanjungbalai - Nida, Khoirun; Arsini, Yenti (UNIVERSITAS PAKUAN, 2025)
This research aims to determine the effectiveness of group counseling with the Dispute Cognitive technique in reducing people pleaser behavior in class VIII students of MTsN Kota Tanjungbalai. The research method used is a quantitative research method with a quasi-experimental approach (quasi experiment) with a one group pretest-posttest design. The research sample consisted of 30 students who were selected purposively based on the results of observations and recommendations from BK teachers. The main instrument was a Likert scale questionnaire that measured six aspects of people pleaser behavior. The results showed a decrease in the average score from 40.10 (pretest) to 35.07 (posttest), and the Wilcoxon test showed a significance value of 0.011 (p 0.05), which means there was a significant difference before and after treatment. These findings indicate that the Dispute Cognitive technique is effective in helping students change irrational thinking patterns to be more rational and build healthy social behavior. This study provides important implications for guidance and counseling services in schools to develop cognitive interventions that focus on strengthening students' identity and assertiveness.